Il dispositivo sacrificale strumento della morte e della vita - Destro, Adriana 1937- (2001)
An anthropological theory of sacrifice first of all requires a theory of ritual. Secondly, the rituals can be understood only within cultures in which they exercise their own social functions. In weak societies a fixed organization of sacrificial arrangements may be absent. It is rare that a specific function is entrusted only to sacrifice. In strong societies, on the contrary, sacrifice is strongly structured and its function clearly defined. The main characteristic of the sacrificial ritual is that it consists in bringing death to a victim who by definition is innocent. This means that sacrifices are rituals through which cultures try to construct the means to dominate or assume control over life and death. To bring death, and control life, is in the power of supernatural forces. Sacrifice enables people to place themselves in relation to the supernatural forces that have this power.
Keywords: Opfer